Future flight’s dynamic capabilities and circular economy opportunities - Chenyi Liao; Graham Parkhurst; Christopher J. Parker (Sustainable Technology and Entrepreneurship, 2025)
Air transport and logistics are associated with economic growth, but sustainability in aviation is vital to address climate change. This paper examines Future Flight (FF) technology’s adoption, focusing on business dynamics, supply chains, and innovation ecosystems through the Technology-Organisation-Environment (TOE) framework and Dynamic Capabilities (DCs) theory. Analysis of twelve expert interviews identifies key barriers, including technological readiness, cybersecurity, financial limitations, and regulatory gaps. Conversely, drivers like design innovation, human capital, and collaboration present growth opportunities. Emerging business models prioritize software-driven value, niche market collaboration, and co-development. While challenges in material design and recycling persist, integrating Circular Economy (CE) principles offers transformative potential for resource efficiency. The study underscores the need for businesses to strengthen dynamic capabilities, build strategic alliances, and navigate regulatory complexities. By providing actionable insights, it advocates a holistic approach combining regulation, public engagement, and innovation to advance a sustainable FF ecosystem.